FACTORS AFFECTING THAI TOURISTS’ DECISION MAKING IN NOSTALGIA TOURISM - Siratchaya Wongatit, สิรัชญา วงษ์อาทิตย์; Yupawan Vannavanit, ยุพาวรรณ วรรณวาณิชย์ (Dusit Thani College Journal, 2018)
The purposes of this research were to study the behavior and factors affecting Thai tourists’ decision making in Nostalgia Tourism including the differences between personal characteristics and factors affecting Thai tourists’ decision making in Nostalgia Tourism and the relationship between personal characteristics and tourists’ behavior. Data were gathered by using questionnaires from 402 Thai tourists who had visited 3 tourist sites such as Plearnwan Retro Market, Hua Hin Samphannam Floating Market ,and Raruk Hua Hin. Quota selection and convenience selection were used. The statistics for data analysis were percentage, mean, standard deviation, t-test, one-way ANOVA, and chi-square. The results of this study were found that most samples traveled during weekend, on their first time of travelling, learned about Nostalgia Tourism from family/friend. Their transportations were private cars. Most of them came with their family/relatives. The main purposes of touring were traveling and recreation. The expenditure for travelling was about 1,000 baht. They tended to come back here again for sure and promised to introduce more people to join Nostalgia Tourism. Overall, tourists rated moderate satisfaction in Nostalgia Tourism. Thai tourists’ overall opinions about the importance of 7 factors influencing their decision making in Nostalgia Tourism were at high level. The factors were divided into two groups as follows: Group 1 was important at high level, including facility, infrastructure, emotions and feelings, and tourism resources. Group 2 was important at rather high level, including security, advertising and public relations, and learning, respectively. Hypothesis test results were found that Thai tourists with different education levels and occupation had different opinions regarding factors affecting their decisions making in Nostalgia Tourism. Moreover, Age, status, occupation, monthly income, and education levels of Thai tourists were correlated with tourist’ behavior with statistical significance at .05 level.